2019
DOI: 10.2142/biophysico.16.0_220
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of oligomers that characterize low-frequency normal modes

Abstract: Dynamics of oligomeric proteins (one trimer, two tetramers, and one hexamer) were studied by elastic network model-based normal mode analysis to characterize their large-scale concerted motions. First, the oligomer motions were simplified by considering rigid-body motions of individual subunits. The subunit motions were resolved into three components in a cylindrical coordinate system: radial, tangential, and axial ones. Single component is dominant in certain normal modes. However, more than one component is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The low mobility of conserved residues and high mobility of variable residues are consistent with the concept of coupling among sequence, structure, and dynamics variations, which has been validated in several earlier studies. 51,52 Such juxtaposition of sequentially conserved (dynamically constrained) and sequentially variable (dynamically flexible) residues appears to be a design feature to mutually support the respective generic and specific properties of sPLA 2 family members.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The low mobility of conserved residues and high mobility of variable residues are consistent with the concept of coupling among sequence, structure, and dynamics variations, which has been validated in several earlier studies. 51,52 Such juxtaposition of sequentially conserved (dynamically constrained) and sequentially variable (dynamically flexible) residues appears to be a design feature to mutually support the respective generic and specific properties of sPLA 2 family members.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…At times, a specific measurement was used in an application to specific PSNs and no rationale on choosing a measurement or comparison between measurements was given. Nevertheless, residues with high BC values have been identified in important biological roles such as the inter-subunit interfaces of oligomeric proteins [31] , the stability of the enzymatic core of c-Abl and c-Src kinases [32] , and the conserved (predominantly hydrophobic) residues of cyclophilin A [33] . Furthermore, two studies (using 178 and 283 structures respectively) found that catalytic sites have significantly higher CC values [34] , [35] .…”
Section: Introductionmentioning
confidence: 99%